Strategi Optimalisasi Realisasi Pendapatan Asli Daerah (PAD) Di Kabupaten Lombok Timur Pada Masa Pandemi Covid-19 - Danang Prio Utomo; Muhamad Juaini (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
The purpose of this study is to analyze the strategy for optimizing the realization of the Regional Revenue Agency of East Lombok Regency during the COVID-19 pandemic in increasing PAD revenue. The research method used in this research is descriptive qualitative, research conducted on independent variables without making comparisons and connecting with other variables. Methods of data collection is done by using observation, interviews and documentation. Analysis of the data used is using data collection, data reduction, data presentation to the conclusion. Based on the analysis, information was obtained that there was an increase in PAD receipts in East Lombok Regency during the covid-19 pandemic, which was influenced by PAD sources which significantly affected the covid-19 pandemic. Based on the optimization strategy analysis, it was found that intensification and extensification strategies were carried out, including 1) optimizing human resources by making new innovations during the covid-19 pandemic, 2) optimizing facilities and infrastructure, 3) collecting data on taxpayer objects while looking for new potential PAD, 4) cross-border cooperation. agencies, 5) use of technology, 6) sanctions in the form of reprimands, 7) socialization, 8) incentives for officers. Meanwhile, the exentification strategy carried out included 1) seeking new potential, 2) optimization of roles with BUMD. The inhibiting factors found include 1) the existence of relaxation policies (regulations), 2) Human Resources, 3) Facilities and Infrastructure 4) No sanctions, 4) Public awareness